Case report: Braid-like right coronary artery with chest pain - Wang, Wenbo; Lan, Lan; Hu, Huijuan (Frontiers in Cardiovascular Medicine, 2023)
Braid-like coronary artery is very rare. It is featured by the division of coronary artery into multiple tortuous small channels that later converge into a normal lumen at any segment of the coronary artery. We presented a case that a 27-year-old male patient with chest pain occasionally. In coronary CT angiography (CCTA) and coronary angiography, the braid-like appearance was found in the right coronary artery. After multidisciplinary discussion, it was speculated to be woven coronary artery (WCA).We also conducted a literature review about woven coronary artery.